Notes Towards a History of Aṣe Dawit I (1382–1413) - Kaplan, Steven (Aethiopica, 2002)
Dawit I has received far less attention than either his grandfather ʿAmdä Ṣǝyon I or his son Zärʾa Yaʿǝqob. This comparatively brief article attempts to partially redress the balance. During the more than three decades during which he reigned, Dawit strengthened the religious and political fabric of Ethiopia. By promoting devotion to both the Cross and the Virgin Mary, he provided the Church with two pan-Christian symbols which transcended local rivalries and regional loyalties. These were, moreover, symbols particularly suited to visual representation and hence comparatively easy to propagate among Ethiopia’s largely illiterate population. He did not, however, neglect the role of religious texts. His reign is remembered both for the important translations initiated, most notably Täʾammǝrä Maryam and for original works composed by his close associate Giyorgis of Sägla. Dawit also made great strides in solidifying Church state relations, particularly through his generous land grants, and although he did not succeed in resolving the Ewosṭatian controversy, in the last decade of his rule, he moved towards a pragmatic accommodation. All this would by itself, qualify Dawit as one of the outstanding leaders in Ethiopian history. His military successes, particularly against the Muslims of Adal, can only further cement his reputation.